Дослідження впливу компосту невизначеного складу на родючість ґрунтів - Разно, М. Р.; Пітак, Р. О.; Тихомирова, Тетяна Сергіївна (ФОП Яроченко Я. В., 2024)
Results of study unknown composition compost impact on the different soil types fertility is given in this work. The work uses the soil bioindication method for samples to determine the compost effect on test plants germination and their vegetative development. It was established that, depending on the original soil fertility, compost can both increase fertility by stimulating plant growth and inhibit germination.
Keywords: ґрунт; родючість ґрунту; побутові відходи; компост; типи ґрунтів; органічні відходи